LinkedIn For Dummies - Elad, Joel (Wiley, 2014)
Don't be left out-link up with this fully updated introduction to the Internet's hottest professional networking tool With more than 225 million members from over 200 countries and territories worldwide, LinkedIn.com is an unbeatable self-marketing tool. LinkedIn For Dummies teaches you how to make the most of your LinkedIn.com profile and build connections and relationships within the world's largest professional network. This thorough introduction covers the latest LinkedIn features and how to use this valuable networking tool. Learn how LinkedIn helps you manage relationships and networks, handle recommendations, showcase your skills and endorsements, import contacts, follow thought leaders, cultivate sales leads, find investors, market yourself, and more. Provides valuable tips and explanations to help you build your profile, develop your network, manage invitations, request and write recommendations, and get involved in LinkedIn groups Covers new and improved LinkedIn tools such as endorsements, people follow, company pages, groups, mobile apps, InMail, and LinkedIn Today Answers frequently asked LinkedIn and job searching questions with the clear and helpful style expected of For Dummies books Connections have never been more vital to a successful career, and LinkedIn For Dummies is here to make sure you don't miss out on your next big opportunity!